Minimally invasive endodontics: a literature review (Research, Society and Development, 2021)
Endodontics is the specialty of dentistry that is dedicated to changes in dental pulp and periapical tissues and seeks to analyze their physiology, morphology and pathology, including the biology of normal pulp, etiology, diagnosis, prevention and treatment of pathologies and injuries that reach the pulp, related or not to alterations in the periapex. The traditional endodontic treatment has been argued by professionals after the emergence of the term minimally invasive endodontic treatment, which prioritizes not only removing or reversing the pathology, but also preserving the healthy tooth structure, promoting greater resistance of the tooth structure. The minimally invasive endodontic approach proposes the geometric shape to be similar to the conventional one, the wear on the coronary portion is restricted by the pericervical dentin. One of the requirements to perform the minimally invasive access is the knowledge of the anatomy and morphology of the tooth to be treated, before performing the access, it is necessary to remove cavities and insufficient restorations. The objective of this work is to elaborate a literature review of a narrative nature, investigating the minimally invasive endodontic access and its repercussion, impact, consequences in the endodontic treatment. This is a literature review, based on the collection of scientific articles, carried out in worldwide bibliographic databases: Academic Google, PubMed, Scielo and Bireme. Articles published in English and Portuguese were selected. Minimally invasive endodontics is not safe for endodontic treatment, nor is it resistant to fracture of the dental element, studies have shown the deficiency in other subsequent stages of treatment after minimally invasive approaches, such as disinfection and shaping of root canals and subsequent filling. Contemporary access is an alternative that has been studied to improve the conventional access without causing damage in the other stages, as it is guided by the anatomy and morphology of the root canal system that aims to preserve the tooth structure without disregarding the scientific and biological bases of the endodontics.